2012
DOI: 10.1017/s1751731112000584
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a high-salt diet by ewes during pregnancy alters nephrogenesis in 5-month-old offspring

Abstract: Maternal nutrition during pregnancy can affect kidney development in the foetus, which may lead to adverse consequences in the mature kidney. It was expected that high-salt intake by pregnant ewes would lead to a reduction in foetal glomerular number but that the ovine kidney would adapt to maintain homoeostasis, in part by increasing the size of each glomerulus. Merino ewes that were fed either a control (1.5% NaCl) or high-salt (10.5% NaCl) diet during pregnancy, as well as their 5-month-old offspring, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Previous studies reported that maternal HS diets during pregnancy affected nephrogenesis and altered glomerular number and size and changed expression of key elements of renin-angiotensin system in the offspring kidney [12,22]. The aim of present study was to determine whether renal vascular development could be affected by prenatal HS.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies reported that maternal HS diets during pregnancy affected nephrogenesis and altered glomerular number and size and changed expression of key elements of renin-angiotensin system in the offspring kidney [12,22]. The aim of present study was to determine whether renal vascular development could be affected by prenatal HS.…”
Section: Discussionmentioning
confidence: 90%
“…Apesar de não existir significância estatística, esses resultados sugerem atenção durante a interpretação de análises deste eletrólito nos animais. Para os íons clore- (Tay et al 2012), e especial atenção deve ser dada aos níveis de cloretos por essa espécie animal. Os ní-veis de cloro também estão diretamente ligados à ingestão de sal mineral, e, como o consumo de sal pelos animais desta faixa etária é menor que nas demais (Oliveira 2011), esse resultado sugere que animais mais jovens devem possuir intervalo de referência diferenciado para os íons cloretos.…”
Section: Discussionunclassified
“…Consumption of a high-salt diet by pregnant ewes during the final phase of nephrogenesis reduces the number of nephrons in the offspring [68]. Similarly in rats, exposure to maternal high dietary salt intake during pregnancy and lactation periods compromises nephrogenesis in the offspring [24].…”
Section: Maternal Sodium Overload During Gestation and Nephron Numbermentioning
confidence: 99%